H∞ CONTROL BASED ROBUST POWER SYSTEM STABILIZER FOR STABILITY ENHANCEMENT (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
A robust H∞ output feedback control approach is used to design power system stabilizers (PSS) for damping electrical power low-frequency oscillations over a wide range of operating conditions. Two H∞ control schemes have been employed in the Single-Machine connected to an infinite bus (SMIB) system. The proposed stabilizers offer robust stability against different unknown loads, considered an external disturbance. The simulation results show good performance and stability enhancement. The effectiveness of the proposed approach is demonstrated by a comparative study with three other approaches: conventional PSS and robust power system stabilizers based on quantitative feedback theory (QFT).
Keywords: Power system stabilizer; H∞ approach; Single-machine system; Low-frequency oscillations